Supercontinuum high-speed cavity-enhanced absorption spectroscopy for sensitive multispecies detection - Werblinski, Thomas; Lämmlein, Bastian; Huber, Franz; Zigan, Lars; Will, Stefan (Optics Letters, 2016)
Cavity-enhanced absorption spectroscopy is promising for many applications requiring a very high concentration sensitivity but often accompanied by low temporal resolution. In this Letter, we demonstrate a broadband cavity-enhanced absorption spectrometer capable of detection rates of up to 50 kHz, based on a spatially coherent supercontinuum ( SC) light source and an in-house-built, high-speed near-infrared spectrograph. The SC spectrometer allows for the simultaneous quantitative detection of CO2, C2H2, and H2O within a spectral range from 1420 to 1570 nm. Using cavity mirrors with a specified reflectivity of R = 98.0 +/- 0.3% a minimal spectrally averaged absorption coefficient of alpha(min) = 1 . 10(-5) cm(-1) can be detected at a repetition rate of 50 kHz. (C) 2016 Optical Society of America